Audit Sistem Informasi Akuntansi Siklus Pengeluaran pada PT. Lagio Furniture - Wicaksono, Aries (Bina Nusantara University, 2014)
Rapid technological developments make the whole thing easier. Many companies also take advantage of these technological developments. Similarly, the corporate accounting system that uses the benefits of information technology in the form of Accounting Information Systems (AIS). PT. Lagio Furniture is amanufacturing company that produces furniture for the premium class. Information system is an important part that helps the companys operations become more effective and efficient, therefore it is important for information systems running properly.This research aimed to audit the general control and applications control on the expenditure cycle accounting information system at PT. Lagio Furniture. This type of audit is audit around the computer. And then also collecting data through observation and interviews with relevant parties. Results of thereserarch is the expenditure cycle accounting information system at PT. Lagio Furniture was good. But there is still need to be improved in the control plan security, operational management control, and control inputs.